2006
DOI: 10.1002/adem.200500095
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH of Phosphating Bath on the Zinc Phosphate Coating on AZ91D Magnesium Alloy

Abstract: Magnesium alloy has some advantageous properties including low density and high strength to weight ratio, [1] high thermal conductivity, good electromagnetic features and being easily recycled. These properties make it valuable in a number of industrial fields including automobile, aerospace components, mobile phones and sporting goods. [2][3][4][5][6][7] For example, the use of magnesium alloys can significantly decrease the weight of automobiles without sacrificing structural strength.When magnesium alloys … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…In a systematic study by Li et al, 56 the effect of the pH of the bath on zinc-phosphated magnesium was investigated. The pH was changed over a wide range, and it was found that lower pH values (between 2·05 and 2·5) significantly improved the coating microstructure from flake-cluster morphology to slab-like feature indicating a more coverage on the surface (Figure 4).…”
Section: Effect Of the Ph Of The Bathmentioning
confidence: 99%
“…In a systematic study by Li et al, 56 the effect of the pH of the bath on zinc-phosphated magnesium was investigated. The pH was changed over a wide range, and it was found that lower pH values (between 2·05 and 2·5) significantly improved the coating microstructure from flake-cluster morphology to slab-like feature indicating a more coverage on the surface (Figure 4).…”
Section: Effect Of the Ph Of The Bathmentioning
confidence: 99%
“…The concentration of reactants, especially accelerators used in the phosphating bath, affects the crystal size and morphology of the coating to some extent [27]. The pH of phosphating bath has a strong affect on characteristics of the coating, too [31]. It is vital in determining the rate and the amount of coating formed [32].…”
Section: Pretreatment Process Prior To Pccmentioning
confidence: 99%
“…Deposition of phosphate conversion coatings has been explored by many researchers as a surface modification method to improve the corrosion resistance of Mg and its alloys (Hu, Meng, Chen, & Wang, 2012;Li, Lian, Niu, & Jiang, 2006; Van Phuong, Lee, Chang, Kim et al, 2013;Xu, Zhang, & Yang, 2009). Deposition of a Zn phosphate coating is one of the most well-studied systems and was recently reviewed by Van Phuong, Lee, Chang, Kim et al (2013).…”
Section: Phosphate Conversion Coatingsmentioning
confidence: 99%
“…Deposition of a Zn phosphate coating is one of the most well-studied systems and was recently reviewed by Van Phuong, Lee, Chang, Kim et al (2013). Being a conversion coating, the resultant phosphate coating is porous in nature, which limits its fullest potential in improving the corrosion resistance of Mg alloys (Hu et al, 2012;Li et al, 2006 (Chen, Birbilis, & Abbott, 2011;Wang, Huang et al, 2013). Being a conversion coating, the resultant phosphate coating is porous in nature, which limits its fullest potential in improving the corrosion resistance of Mg alloys (Hu et al, 2012;Li et al, 2006 (Chen, Birbilis, & Abbott, 2011;Wang, Huang et al, 2013).…”
Section: Phosphate Conversion Coatingsmentioning
confidence: 99%